Inovasi pembelajaran berbasis digital melalui Liveworksheet untuk membudayakan keterampilan digital peserta didik - Trisakti Handayani; Fahdian Rahmandani; Achmad Muzzaki (University of Muhammadiyah Malang, 2023)
Technological transformation in education challenges teachers' pedagogical thinking. Teachers are required to be experts in learning technology in working with students. This present study aims to develop a Liveworksheet-based LMS; and investigate the functions and practicality of the LMS Liveworksheet for Science lesson in the 6th grade. The employed methodology was Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) stage model. The data were obtained through questionnaires, observations, interviews, and documentation. The results indicate that the developed Liveworksheet LMS was validated by both material and media experts with the feasibility and practical validation tests of 90%. Meanwhile, the functional and substance validation tests were 85%, qualified as highly valid. Based on the questionnaire responses, 80% students scored valid, indicating that and the LMS was suitable for use. The post-test results were averagely 87%, showing a very good (effective) criteria. This finding reveals that the resulting LMS Liveworksheet is feasible, practical, functional, and substantial for learning, and is effective to improve student learning outcomes. It is implied that the development of the LMS Liveworksheet is important generate interactive content, such as open discussion forums where students can be more enthusiastic and active in learning through the LMS